Enhancing problem-solving skills in chemistry through problem-based learning with SETS: a systematic review - Mulyani, Pangastuti Sri; Heliawati, Leny (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
The development of 21st-century education in Indonesia necessitates equipping students with essential competencies such as problem-solving skills (PSS), particularly in chemistry learning, where real-world relevance is crucial. This study explores the integration of the Science, Environment, Technology, and Society (SETS) approach into Problem-Based Learning (PBL) as a strategy to enhance students' PSS in chemistry. Employing a Systematic Literature Review (SLR), this research analyzed 127 articles from five databases (SCOPUS, Google Scholar, Semantic Scholar, Taylor & Francis, and ERIC) published between 2020 and 2024. After applying inclusion and exclusion criteria based on relevance to PBL, SETS, PSS, and secondary chemistry education, 14 high-quality articles were selected for in-depth analysis. The review revealed that integrating SETS into PBL positively impacts students' ability to analyze, reason, and apply chemical concepts in solving contextual problems. However, challenges such as teacher readiness, curriculum constraints, and limited assessment tools were also identified. This study contributes to the literature by mapping trends and identifying best practices for implementing PBL-SETS in chemistry education. Despite its comprehensive scope, the review is limited by potential publication bias and the exclusion of non-English studies. These findings suggest the need for more empirical studies and professional development programs to support teachers in adopting PBL-SETS effectively.